Please Pass the Translanguaging: The Dinner Table Experience in the Lives of Newcomer Canadian Deaf Youth and Their Families - Joanne Catherine Weber; Chelsea Temple Jones; Abneet Atwal (Languages, 2023)
While translanguaging occurs in the homes of deaf people and their hearing family members who do not sign or possess limited signing skills, in this article we argue that translanguaging alone does not explain the complex, domestic-sphere language experiences of three young, newcomer artists in Saskatchewan, Canada. We frame our inquiry around the “dinner table experience” phenomenon, wherein deaf family members receive partial or little access to conversational exchanges. At the dinner table, which is both a literal setting and a metaphor for exclusion experienced by deaf people in audiocentric cultures, many deaf family members report feeling loved yet disconnected. However, translanguaging serves to expand linguistic repertoires among hearing and deaf interlocutors amidst the dinner table experience. We draw from three interviews with deaf youth who describe the dinner table experience through both dialogue and art making, including descriptions of ways in which communication is facilitated or not facilitated, thereby highlighting available and unavailable translanguaging practices in the domestic sphere. The interview data suggest that the dinner table experience is a significant setting for translanguaging, and that promoting accessible and equitable translanguaging practices in the home remains a significant challenge, especially when combined with newcomer lived experience that does not always match current descriptions of translanguaging. We posit that translanguaging is a necessary practice among hearing and deaf persons at the table that can and should be expanded to consider the intersectional experiences of communicators in this literal and metaphorical setting.